2012
DOI: 10.1111/j.1469-8986.2012.01381.x
|View full text |Cite
|
Sign up to set email alerts
|

P1and beyond: Functional separation of multiple emotion effects in word recognition

Abstract: Event-related potentials (ERPs) revealed effects of emotional meaning on word recognition at distinguishable processing stages, in rare cases even in the P1 time range. However, the boundary conditions of these effects, such as the roles of different levels of linguistic processing or the relative contributions of the emotional valence and arousal dimensions, remain to be fully understood. The present study addresses this issue by employing two tasks of different processing demands on words that orthogonally v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
142
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(171 citation statements)
references
References 74 publications
16
142
4
Order By: Relevance
“…The results of Briesemeister et al (2014) already supported this hypothesis: An early N1 effect, discussed as indexing early attentional resource allocation to affectively conditioned word forms (Bayer et al, 2012), was found to separate high-from low-happiness words, whereas positivity affected the N400 and the LPC. Both of the latter components are associated with explicit affective evaluation.…”
Section: Discussionsupporting
confidence: 71%
“…The results of Briesemeister et al (2014) already supported this hypothesis: An early N1 effect, discussed as indexing early attentional resource allocation to affectively conditioned word forms (Bayer et al, 2012), was found to separate high-from low-happiness words, whereas positivity affected the N400 and the LPC. Both of the latter components are associated with explicit affective evaluation.…”
Section: Discussionsupporting
confidence: 71%
“…However, note that this overall U-shaped distribution involves a particularly strong negative linear correlation of arousal with valence within the domain of negative words, which sometimes leads to an overall negative linear correlation (e.g., Citron et al, 2014b;Schmidtke et al, 2014;Võ et al, 2009). Highly arousing words are processed faster and more accurately and elicit stronger neural responses than nonarousing words, when valence is kept constant (Bayer, Sommer, & Schacht, 2012;Hofmann, Kuchinke, Tamm, Võ, & Jacobs, 2009;Recio et al, 2014). Nevertheless, emotional valence seems to be a stronger predictor of response speed and accuracy than arousal (Estes & Adelman, 2008;Kousta et al, 2009).…”
Section: The Psycholinguistic Characteristics Of Idiomsmentioning
confidence: 96%
“…There is evidence that emotional content influences ERPs to words during early time windows such as the P1 time window (80-120 ms; Bayer, Sommer, & Schacht, 2012;Bernat, Bunce, & Shevrin, 2001;Junghöfer, Bradley, Elbert, & Lang, 2001;Li, Zinbarg, & Paller, 2007;Scott, O'Donnell, Leuthold, & Sereno, 2009), and that involuntary attention allocation in the visual cortex is not limited to pictorial stimuli, but can occur for word stimuli which have only arbitrary relationships between their visual features and corresponding meaning (Bayer, et al, 2012;Ortigue et al, 2004;Rabovsky, Sommer, & Abdel Rahman, 2011). …”
Section: Erp Studies Of Threat Processing In Clinical Anxietymentioning
confidence: 99%
“…Alternatively, nonlinguistic mechanisms may contribute to early emotion effects, such as feature detection or associative learning processes that do not depend on lexical access (Bayer, et al, 2012).…”
Section: Erp Studies Of Threat Processing In Clinical Anxietymentioning
confidence: 99%